2011
DOI: 10.1080/14786435.2011.561811
|View full text |Cite
|
Sign up to set email alerts
|

Dilatational viscoplasticity of polycrystalline solids with intergranular cavities

Abstract: We propose constitutive models for polycrystalline aggregates with intergranular cavities and test them against full-field numerical simulations. Such conditions are prevalent in many engineering applications and failure of metallic components (e.g. HIPing and other forming processes, spallation under dynamic loading conditions, etc.), where the dilatational effects associated with the presence of cavities must be accounted for, and standard polycrystalline models for incompressible plasticity are not appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 61 publications
2
36
1
1
Order By: Relevance
“…Among these applications, it is worth mentioning a recent study on dilatational plasticity of porous polycrystalline materials, 21 in which the effect of the crystallinity (and heterogeneity) of the material surrounding intergranular voids on the growth of such voids was for the first time assessed and quantified, and compared with homogenization approaches.…”
Section: Formulationmentioning
confidence: 99%
“…Among these applications, it is worth mentioning a recent study on dilatational plasticity of porous polycrystalline materials, 21 in which the effect of the crystallinity (and heterogeneity) of the material surrounding intergranular voids on the growth of such voids was for the first time assessed and quantified, and compared with homogenization approaches.…”
Section: Formulationmentioning
confidence: 99%
“…On the other hand, classic self-consistent formulations [27][28][29][30], which are extensively used to estimate the viscoplastic response of fully dense polycrystals, have been recently extended to the case of voided polycrystals [31]. These new homogenization formulations, based on the variational theories of Ponte Castañ eda [32,33] and previous applications of the latter to cases of voids in a nonlinear matrix [34,35], are better suited to handle the strong mechanical contrast in the voided aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Note that an outer bound on v P induces an upper bound on s 0 . The results presented below correspond to 200 crystal orientations (N = 200) prescribed according to a Sobol sequence Sobol (1967) in order to generate textures as close as possible to isotropy-see Lebensohn et al (2011). In any event, the exact same set of orientations were used for all computations so that comparisons between the different bounds are meaningful.…”
Section: Results For Cubic and Hexagonal Polycrystalsmentioning
confidence: 99%
“…Given that these are materials with a strong heterogeneity contrast, the question arises as to whether larger differences between the non-relaxed and relaxed linear-comparison bounds will appear in the context of (two-phase) polycrystalline voided solids where the overall heterogeneity contrast is infinitely strong. Such bounds would help current efforts directed towards developing micromechanical models for voided polycrystals to incorporate texture effects in ductile-failure theories of engineering alloys-see Lebensohn et al (2011)-calculations are now underway and will be reported upon completion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation